Bone marrow macrophage‐derived exosomal miR‐143‐5p contributes to insulin resistance in hepatocytes by repressing MKP5. (14th October 2021) - Li, Linfang; Zuo, Huiyan; Huang, Xiuqing; Shen, Tao; Tang, Weiqing; Zhang, Xiaoyi; An, Tong; Dou, Lin; Li, Jian
Abstract: Objective: In this study, we aim to explore the role of bone marrow macrophage‐derived exosomes in hepatic insulin resistance, investigate the substance in exosomes that regulates hepatic insulin signalling pathways, reveal the specific molecular mechanisms involved in hepatic insulin resistance and further explore the role of exosomes in type 2 diabetes. Materials and methods: High‐fat diet (HFD)‐fed mice were used as obesity‐induced hepatic insulin resistance model, exosomes were isolated from BMMs which were extracted from HFD‐fed mice by ultracentrifugation. Exosomes were analysed the spectral changes of microRNA expression using a microRNA array. The activation of the insulin signalling pathway and the level of glycogenesis were examined in hepatocytes after transfected with miR‐143‐5p mimics. Luciferase assay and western blot were used to assess the target of miR‐143‐5p. Results: BMMs from HFD‐fed mice were polarized towards M1, and miR‐143‐5p was significantly upregulated in exosomes of BMMs from HFD‐fed mice. Overexpression of miR‐143‐5p in Hep1‐6 cells led to decreased phosphorylation of AKT and GSK and glycogen synthesis. Dual‐luciferase reporter assay and western blot demonstrated that mitogen‐activated protein kinase phosphatase‐5 ( Mkp5, also known as Dusp10 ) was the target gene of miR‐143‐5p. Moreover, the overexpression of MKP5 could rescue the insulin resistance induced by transfection miR‐143‐5p mimics in Hep1‐6. Conclusion: Bone marrow macrophage‐derived exosomal miR‐143‐5p induces insulin resistance in hepatocytes through repressing MKP5. Abstract : Up‐regulated miR‐143‐5p in BMM exosomes could be passed to hepatocytes and impaired hepatic glycogenesis by targeting Mkp5 .